Penentuan Rute Distribusi Pengiriman Hemodialisa Pack Untuk Menurunkan Biaya dan Waktu Pengiriman Dengan Menggunakan Metode Vehicle Routing Problems - S, Dina Sari Dewi; Asmungi (Jurnal Teknologi dan Manajemen Sistem Industri, 2023)
PT. Raska Jaya Medika is a medical equipment supplier specializing in Hemodialisa Packs, located at Ruko De Farda RK-1, Keboan Anom Village, Gedangan District, Sidoarjo, East Java. The Hemodialisa Pack functions to filter and cleanse harmful metabolic substances from the body. Considering the high demand with random patterns and dispersed locations, a revision of the distribution route is necessary for greater efficiency. The author analyzes the route using a single vehicle, applying the sweep algorithm to form customer clusters, followed by mixed integer linear programming (MILP) to determine the optimal route without exceeding vehicle capacity. The MILP model results indicate a cost saving of Rp451,719 (4.31%), a time efficiency of 1.070%, and a distance efficiency of 1.018%.